2019
DOI: 10.3390/ijms20184600
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal MiRNAs in Pediatric Cancers

Abstract: MicroRNAs (miRNAs) have generated great attention in oncology as they play a fundamental role in the regulation of gene expression and their aberrant expression is present in almost all types of tumors including pediatric ones. The discovery that miRNAs can be transported by exosomes, which are vesicles of 40-120 nm involved in cellular communication, that are produced by different cell types, and that are present in different biological fluids, has opened the possibility of using exosomal miRNAs as biomarkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 146 publications
0
38
0
1
Order By: Relevance
“…The above results suggested that circ_0000527 was involved in promoting the progression of RB and demonstrated that it had an important role in RB. MiRNAs are also reported to be engaged in the regulation of the tumorigenesis and progression of a variety of human tumors [25,26]. MiR-646 is regarded as a tumor suppressor in many human cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above results suggested that circ_0000527 was involved in promoting the progression of RB and demonstrated that it had an important role in RB. MiRNAs are also reported to be engaged in the regulation of the tumorigenesis and progression of a variety of human tumors [25,26]. MiR-646 is regarded as a tumor suppressor in many human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are also reported to be engaged in the regulation of the tumorigenesis and progression of a variety of human tumors [ 25 , 26 ]. MiR-646 is regarded as a tumor suppressor in many human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are emerging as new circulating biomarkers in the liquid biopsy field. Cell membrane-derived nanovesicles (30–100 nM in diameter), containing RNA, microRNA, lipids and proteins, exosomes are released by several cell types and mainly by tumor cells [ 9 , 87 , 88 ]. The possibility to isolate exosomes from different sources, as well as to monitor their content in a relatively simple way, allows one to follow tumor evolution and evaluate the response to therapy over time.…”
Section: Discussionmentioning
confidence: 99%
“…The various roles played by miRNA in neoplasia have been continuously reported and confirmed [109]. Their potential use as circulating biomarkers has been widely speculated, either as cell-free miRNA or when included as vesicle cargo [110][111][112].…”
Section: Small-ev Cargo As Disease Markersmentioning
confidence: 92%